PENGARUH MODIFIKASI PEMBERIAN GARAM TERHADAP TINGKAT KECUKUPAN ENERGI, PROTEIN, LEMAK, KARBOHIDRAT, TEKANAN DARAH SISTOLE DAN DIASTOLE PADA PASIEN HIPERTENSI DI RSUD dr R GOETENG TAROENADIBRATA PURBALINGGA - Riana Wulandari; Setyo Prihatin; Ana Yuliah Rahmawati (Poltekkes Kemenkes Semarang, 2017)
Background: Average food waste in hypertensive patients who underwent inpatient in RSUD dr R Goeteng is 50%, it shows that intake of hypertensive patient is still less. The above problems can be solved one of them by modification of salt so that.Objective: To know the difference of energy sufficiency level, protein, fat, carbohydrate, blood pressure of sistole and diastole before and after given modification of salt in hypertension patient in RSUD dr. R Goeteng Taroenadibrata Purbalingga.Methods: Experimental research with posttest only control group design. The subjects of this study were hypertensive patients, amounting to 30 patients divided into 2 groups: 15 control groups and 15 treatment groups. Method of data retrieval is by looking at the remaining food of patients to calculate the level of adequacy of energy, protein, fat, carbohydrate. Modification of salt given for 3 days.Results:. There were differences in salt modification to the level of energy sufficiency (P = 0.042), protein adequacy (p = 0.02), fat sufficiency rate (p = 0.018), carbohydrate adequacy (p = 0.033), systole blood pressure p = 0.037), blood pressureConclusion: Salt modification is a factor that affects the sufficiency level of energy, protein, fat, carbohydrate, sistole blood pressure, and diastolic blood pressure in hypertensive patients in RSUD dr R Goeteng Taroenadibrata Purbalingga.